Gambaran Epidemiologi dan Evaluasi Sistem Surveilans Kesehatan Jiwa di Puskesmas Cilembang Kota Tasikmalaya Tahun 2024 - Septiani Tri Windianti; Rini Handriani; Anuy Nurofiat; Mala Nur’aeni (STIKES Columbia Asia Medan, 2025)
Mental health is an important indicator of the overall public health status. Mental health surveillance through screening serves as a strategy for early detection of mental disorders and continuous case monitoring. In Indonesia, approximately 630,827 individuals or about 2.0% of the population aged >15 years are reported to have mental health problems based on provincial data. This study was conducted at Cilembang Public Health Center, Tasikmalaya City, using a mixed-method approach that combines quantitative and qualitative methods. The quantitative sample was selected using total sampling, involving 35 new cases of people with mental disorders (ODGJ) recorded in 2024. Meanwhile, qualitative subjects were selected through purposive sampling, involving surveillance officers engaged in the mental health program. The qualitative findings cover the input, process, and output components of the surveillance implementation. Results show that the mental health surveillance program at Cilembang PHC is supported by various health personnel, funding from the BOK program, and the SIMKESWA digital system integrated with the Ministry of Health. Active surveillance is carried out through community and school screenings using the SDQ and SRQ-20 instruments, followed by diagnosis, counseling, and initial management. The program exceeded the target for identifying severe ODGJ cases. However, screening among individuals aged ≥15 years has not been optimally implemented due to competing program priorities.